Pancreatitis is frequent among patients with side-branch intraductal papillary mucinous neoplasia diagnosed by EUS - Azar, Riad (2009)
Background Because of greater recognition and improved imaging capabilities, intraductal papillary mucinous neoplasms (IPMNs) are being diagnosed with increasing frequency. IPMNs of the main pancreatic duct cause symptoms and lead to pancreatitis. Side-branch (SB) IPMNs are thought to cause symptoms less frequently, and their association with pancreatitis is not well defined. Objective Our purpose was to ascertain whether an association exists between SB-IPMN and pancreatitis. Design Single-center, retrospective study. Setting Academic medical center. Patients A total of 305 patients underwent EUS examinations between October 2002 and October 2006 for pancreatic cystic lesions. Main Outcome Measurement The main outcome measure was the frequency of acute or chronic pancreatitis that was not procedurally related. Results Thirty-two patients had SB-IPMNs, and 11 (34%) had pancreatitis. Three patients reported a single episode, and 8 patients reported having recurrent episodes of pancreatitis. Overall, 17 (53%) patients had symptoms possibly attributable to SB-IPMN. Female sex (73% vs 38%) and multiple pancreatic lesions (54% vs 24%) were more commonly seen in those with pancreatitis, but were not statistically significant factors. Larger cyst size or cyst fluid marker levels did not appear associated with pancreatitis occurrence. EUS-FNA demonstrated communication with the pancreatic duct in 94% and thick, mucinous fluid in 84%. Limitations Single-center, retrospective study. Conclusions Pancreatitis was frequently associated with the presence of SB-IPMNs in our referral practice. SB-IPMNs should be considered in the differential diagnosis of patients with recurrent pancreatitis with cystic lesions seen on imaging studies. EUS-FNA was the most useful modality in helping to differentiate SB-IPMNs from other lesions.